Pengaruh Gamifikasi pada Materi Sumber Energi Alternatif terhadap Motivasi Belajar dan Sikap Percaya Diri Siswa - Ridhaningtyas, Latifa Putri (Lembaga Yasin AlSys, 2025)
This study aims to evaluate the effect of gamification on students' learning motivation and self-confidence. The underlying problem is low learning motivation due to monotonous conventional learning methods. Using the PRISMA method, this study screened relevant literature and used a quantitative approach with an experimental design. The research subjects were 60 grade 5 students, who were divided into an experimental group (using Kupin Edu) and a control group (using traditional methods). Data were collected through pretest and posttest questionnaires, analyzed by statistical tests. The results showed that the experimental group experienced significant improvements in learning motivation, from a score of 65.3 to 82.7, and self-confidence, from 58.7 to 75.3. In contrast, the control group showed minimal improvement. Competitive elements, such as leaderboards, and collaborative elements, such as daily challenges, were shown to significantly increase student engagement. This study concludes that gamification is an effective approach to increase students' learning motivation and confidence, particularly at the primary education level. The practical implication is that gamification can be integrated in the curriculum to create a more engaging and relevant learning environment. This research contributes to expanding the application of educational technology to improve the quality of student learning.